Factors associated with Mycobacterium avium subsp. paratuberculosis in dairy cows from Northern Antioquia, Colombia - Fernández Silva, Jorge A.; Ramírez Vásquez, Nicolás F.; Correa Valencia, Nathalia M. (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: Johne´s disease (JD) is a severe enteritis that affects ruminants and has been diagnosed in cattle and sheep in Colombia. However, epidemiological information on the disease in this country is scarce. Objective: to identify factors associated with the JD serum enzyme-linked immunosorbent assay (ELISA) status of dairy cows. Methods: a cross-sectional study was carried out in 307 asymptomatic adult Holstein dairy cows from 14 herds in nine districts of Belmira and San Pedro de los Milagros municipalities during November, 2007. Nineteen to 29 cows, ≥ 2 years of age were randomly selected and blood sampled from every herd. A commercial ELISA kit was used to analyze sera. Information regarding cow related factors (age, farm-born, parity, and daily milk yield) and herd management practices (i.e. herd size, herd average milk production, current presence of symptomatic animals, cattle purchase, own animals grazing in foreign pastures, feeding of calves before weaning, manure spread on pastures, and sighting of birds in feed storing areas) was collected using questionnaires. Descriptive statistics were computed for all variables and a multivariable logistic regression model was constructed (p<0.05). Results: ten percent (31/307; 95% CI: 7-14%) of the animals were positive by ELISA. In 70% (10/14) of the herds, ELISA detected at least one positive animal. Cow and herd factors such as “parity” and “feeding of calves before weaning” showed weak and strong associations with ELISA positive results, respectively. The odds ratio (OR) for JD seropositivity increased 20% (OR = 1.20; 95% CI: 0.98-1.47; p = 0.067) in cows with > 1 parity. The OR was 0.74 times lower (OR = 0.26; 95% CI: 0.096-0.70; p<0.01) in herds feeding calves with pooled colostrum from several cows, compared to herds feeding calves with colostrum from their own dams. Conclusion: JD seroprevalence was 10 and 70% at animal and herd-level, respectively. Cow and herd factors “parity” and “feeding of calves before weaning” showed weak and strong association with positive results, respectively.